The Grapsidae and Ocypodidae (Decapoda: Brachyura) of Tanzania - Hartnoll, R. G. (J. Zool. London, 1975)
Twenty-nine species of the Grapsidae and 15 species of the Ocypodidae were collected from the littoral zone in the area around Dar es Salaam. Nine species of grapsidae and three of Ocypodidae were new records for the East African area, bringing the total of recorded species for the region to 35 and 26 respectively. The distribution of these crabs indicates a very limited endemism in the western Indian Ocean, with the majority of species forming an attenuated extension of the abundant Indo/West Pacific brachyuran fauna. The habitat preference of each species is described. Within each subfamily there is a relative uniformity in general habitat preference, mode of life and manner of feeding. The species of each subfamily are then separated by substrate choice and preferred level on the shore. The greatest numbers of species occur in the most diverse habitats - the creek mangrove, the coastal mangrove and the reef flat.